Stereoselective synthesis of ophiocerins A and C - Show, Krishanu; Gupta, Priti; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
An efficient synthesis of ophiocerins A and C has been achieved via a common intermediate. The stereogenic centers were generated by means of Jacobsen's hydrolytic kinetic resolution and Sharpless kinetic resolution. (C) 2011 Elsevier Ltd. All rights reserved.